Can Tests Based on Option Hedging Errors Correctly Identify Volatility Risk Premia? - Branger, Nicole; Schlag, Christian (Journal of Financial and Quantitative Analysis, 2008)
Abstract Tests for the existence and the sign of the volatility risk premium are often based on expected option hedging errors. When the hedge is performed under the ideal conditions of continuous trading and correct model specification, the sign of the premium is the same as the sign of the mean hedging error for a large class of models. We show that discrete trading and model misspecification may cause the standard test to yield unreliable results. In particular, ignoring jump risk premia can lead to incorrect conclusions. We also show that delta-gamma hedges do not increase the reliability of the test.